Intensity of leaf diseases, productivity, thousand grain weight and spotted grains in response to the number of fungicide applications on irrigated rice cultivar SCS 116 satoru Intensidade de doenças foliares, produtividade, massa de mil grãos e grãos manchados em resposta ao número de aplicações de fungicida no cultivar de arroz irrigado SCS 116 Satoru - Bordin L.C.* (2014)
© 2014, Universidade Estadual Paulista (UNESP). All rights reserved.The occurrence of leaf diseases in irrigated rice can reduce the yield and the grain quality. The aim of this study was to quantify the response of fungicide application number on leaf disease intensity, productivity, thousand grain weight and spotted grain in irrigated rice. Experiments were conducted with cultivar SCS 116 Satoru in 2011/12 and 2012/13 growing seasons in the city Rio do Oeste, located in Alto Vale do Itajai, Santa Catarina State. Experimental design was in randomized blocks, with four replicates and six treatments constituted of a mixture of fungicides triazole (difenoconazole) and strobilurin (azoxystrobin) in one application at the end of tillering (V8), two applications (V8 + R0, panicle initiation), three applications (V8 + R0 + R2, booting), four applications (V8 + R0 + R2 + R4, flowering), five applications (V8 + R0 + R2 + R4 + R6, milky grain) and no application (control). Before each application, the incidence and the severity of leaf diseases were determined. In the two seasons, predominant leaf diseases were blast, brown spot and scald. The increase from one to five fungicide applications presents a significant response in reducing the intensity of leaf diseases, with an average increase of 19.5%, 30%, 70.3%, 86.6% and 100.8% in productivity and 0.2%, 13.7%, 28.5%, 41.3% and 54% in thousand grain weight, as well as a reduction of 22%, 31.8%, 44.1%, 75.9% and 168.5% in spotted grains, compared to control.